2022
DOI: 10.1371/journal.pone.0273933
|View full text |Cite
|
Sign up to set email alerts
|

FCGR3A gene duplication, FcγRIIb-232TT and FcγRIIIb-HNA1a associate with an increased risk of vertical acquisition of HIV-1

Abstract: Background Some mother-to-child transmission (MTCT) studies suggest that allelic variations of Fc gamma receptors (FcγR) play a role in infant HIV-1 acquisition, but findings are inconsistent. To address the limitations of previous studies, the present study investigates the association between perinatal HIV-1 transmission and FcγR variability in three cohorts of South African infants born to women living with HIV-1. Methods This nested case-control study combines FCGR genotypic data from three perinatal coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…However, this association did not remain significant when considering age as a covariable. Our findings align with the previously described protective effect of the FCGR2B rs1050501-TT genotype against malaria and infant susceptibility to HIV infection [40,41], but we did not find evidence of its protective role in controlling parasitemia in children analyzed in Burkina Faso, mainly belonging to the Bobo ethnic subgroup. These discrepancies may partly depend on agerelated factors, which manifest differently in adults with a more mature immune response controlling the parasite.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, this association did not remain significant when considering age as a covariable. Our findings align with the previously described protective effect of the FCGR2B rs1050501-TT genotype against malaria and infant susceptibility to HIV infection [40,41], but we did not find evidence of its protective role in controlling parasitemia in children analyzed in Burkina Faso, mainly belonging to the Bobo ethnic subgroup. These discrepancies may partly depend on agerelated factors, which manifest differently in adults with a more mature immune response controlling the parasite.…”
Section: Discussionsupporting
confidence: 89%
“…The lack of association between FCGR2A and FCGR2B coding variants with parasitemia could also be attributed to ethnic variations [51], sample size, or the diversity of observed malaria phenotypes, including parameters such as socioeconomic status, access to healthcare, and control measures in previously described cohorts. Studies on the population diversity of FcγR variants have shown differences in ethnic variation, allele distribution, and linkage disequilibrium at the FCGR gene locus, especially for FCGR2B and FCGR2C, among Kenyan, Nigerian, South African, and Caucasian populations [40,41]. The rs1050501 SNP in FCGR2B has notably been shown to be under malaria-driven selective evolutionary pressure [27], and minor allele frequencies of FcγRIIb-232T and FcγRIIIb-HNA1 FCGR variants associated with protection against clinical malaria were reported to be more prevalent in malariaendemic regions than in non-endemic regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation